Reverse leakage current mechanisms in quantum dot laser structures - Hasbullah, Nurul Fadzlin; David, John P. R. (2011)
Dark current-voltage measurements undertaken on a series of InAs based quantum dot laser structures show significant variations depending on the growth conditions of the GaAs barrier layer. A systematic study of their temperature dependence suggests that the main mechanism determining the reverse leakage is due to generation–recombination via mid-band traps assisted by Frenkel-Poole emission of carriers from these traps. Since the dark current is a relatively parameter to determine in a device, optimising this is a quicker means of optimising the growth parameters than undertaking full laser testing. I. INTRODUCTION